Art Training in Dementia: A Randomized Controlled Trial - Johnson, Katherine G.; D’Souza, Annalise A.; Wiseheart, Melody (Frontiers in Psychology, 2020)
Objectives: The present study explores the effect of visual art training on people with dementia, utilizing a randomized control trial design, in order to investigate the effects of an eight-week visual art training program on cognition. In particular, the study examines overall cognition, delayed recall, and working memory, which show deficits in people with dementia. Method: Fifty-three individuals with dementia were randomly assigned into either an art training (n = 27) or usual-activity waitlist control group (n = 26). Overall cognition and delayed recall were assessed with the Montreal Cognitive Assessment (MoCA), and working memory was assessed with the Backward Digit Span task. Results: There were no group differences in overall cognition, or working memory, while a difference in delayed recall was undetermined, based on post-test – pre-test difference scores. Groups were comparable at baseline on all measures. Conclusions: The measures of cognition, delayed recall, and working memory used in this study were not affected by an eight-week visual art training program. ClinicalTrials.gov identifier: NCT03175822.